Physiological responses to dyadic interactions are influenced by neurotypical adults' levels of autistic and empathy traits - Truzzi, Anna (2017)
Autistic traits are distributed on a continuum that ranges from non-clinical to clinical condition. Atypical responses to social situations represent a core feature of the Autism Spectrum Disorders phenotype. Here, we hypothesize that atypical physiological responses to social stimuli may predict non-clinical autistic and empathy traits levels. We measured physiological responses (heart rate, facial temperature) of 40 adults (20F) while showing them 24 movies representing dyadic interactions. Autistic traits were assessed through Autism Quotient questionnaire (AQ), while empathy traits were measured using the Empathy Quotient questionnaire (EQ). Opposite correlations between AQ and EQ scores and physiological responses were found. Analysis of physiological responses revealed that individuals with better social abilities, low AQ and high EQ, show opposite activation patterns compared to people with high AQ and low EQ. Findings show that physiological responses could be biomarkers for people's autistic traits and social abilities.